The low-density lipoprotein receptor-related protein 1 (LRP1) interactome in the human cornea. (June 2022) - Mogensen, Emilie Hage; Poulsen, Ebbe Toftgaard; Thøgersen, Ida B.; Yamamoto, Kazuhiro; Brüel, Annemarie; Enghild, Jan J.
Abstract: The human cornea is responsible for approximately 70% of the eye's optical power and, together with the lens, constitutes the only transparent tissue in the human body. Low-density lipoprotein receptor-related protein 1 (LRP1), a large, multitalented endocytic receptor, is expressed throughout the human cornea, yet its role in the cornea remains unknown. More than 30 years ago, LRP1 was purified by exploiting its affinity for the activated form of the protease inhibitor alpha-2-macroblulin (A2M), and the original purification protocol is generally referred to in studies involving full-length LRP1. Here, we provide a novel and simplified LRP1 purification protocol based on LRP1's affinity for receptor-related protein (RAP) that produces significantly higher yields of authentic LRP1. Purified LRP1 was used to map its unknown interactome in the human cornea. Corneal proteins extracted under physiologically relevant conditions were subjected to LRP1 affinity pull-down, and LRP1 ligand candidates were identified by LC-MS/MS. A total of 28 LRP1 ligand candidates were found, including 22 novel ligands. The LRP1 corneal interactome suggests a novel role for LRP1 as a regulator of the corneal immune response, structure, and ultimately corneal transparency. Highlights: A novel purification protocol for endogenous human LRP1 is presented. We established the LRP1 interactome in the human cornea. A total of 28 ligand candidates that directly or indirectly interact with LRP1 were identified. Of these 22 are novel LRP1 ligands.